Cooperative Binding of Divalent Diamides by N‐Alkyl Ammonium Resorcinarene Chlorides. Issue 26 (27th May 2015) - Beyeh, N. Kodiah; Ala‐Korpi, Altti; Pan, Fangfang; Jo, Hyun Hwa; Anslyn, Eric V.; Rissanen, Kari
Abstract N‐Alkyl ammonium resorcinarene chlorides, stabilized by an intricate array of hydrogen bonds leading to a cavitand‐like structure, bind amides. The molecular recognition occurs through intermolecular hydrogen bonds between the carbonyl oxygen and the amide hydrogen of the guests and the cation–anion circular hydrogen‐bonded seam of the hosts, as well as through CH⋅⋅⋅π interactions. The N‐alkyl ammonium resorcinarene chlorides cooperatively bind a series of di‐acetamides of varying spacer lengths ranging from three to seven carbons. Titration data fit either a 1:1 or 2:1 binding isotherm depending on the spacer lengths. Considering all the guests possess similar binding motifs, the first binding constants were similar (K1: 102 M−1) for each host. The second binding constant was found to depend on the upper rim substituent of the host and the spacer length of the guests, with the optimum binding observed with the six‐carbon spacer (K2: 103 M−2). Short spacer lengths increase steric hindrance, whereas longer spacer lengths increase flexibility thus reducing cooperativity. The host with the rigid cyclohexyl upper rim showed stronger binding than the host with flexible benzyl arms. The cooperative binding of these divalent guests was studied in solution through 1H NMR titration studies and supplemented by diffusion‐ordered spectroscopy (DOSY), X‐ray crystallography, and mass spectrometry.